"Like special oriental spices added into Western food": An ecological study of an EFL student's literacy autobiography and its pedagogical implications. Issue 3 (6th June 2022) - Yang, Shizhou
Abstract : Little is known about literacy autobiography (LA) in the English as a foreign language (EFL) context. Using the triad of translingualism, transnationalism, and investment as a lens to examine the classroom writing ecology (which is composed of the participants, process, artifacts, and structure), the present ethnographic case study explores a Chinese graduate student's LA writing in a writing course for translators. Data include multiple drafts, weekly journals, interviews, and course documents. The researcher found that the classroom writing ecology had a great impact on the student's LA writing. Although transnationalism did not directly motivate her to invest in LA writing, it informed her writing in significant ways, and her sustained investment in LA writing culminated in strong signs of translingualism in her final draft. This study contends that translingualism and transnationalism are both relevant in EFL literacy education. It also contributes new knowledge on the pedagogical use of LA to facilitate EFL learners' acquisition of academic literacy and to nurture their translingual subjectivity. In adopting LA in EFL writing education, teachers are encouraged to provide a classroom writing ecology that supports multilingual students' LA‐mediated identity work by embracing a resource perspective on students' prior literacy experiences, a dialogical pedagogy, and a research‐oriented, multidraft approach.